The rise of a pandemic-related writing style in the news media - Mior Kamarulbaid, Afiqah; Wan Abas, Wan Anita; Omar, Siti Zobidah; Bidin, Rosmiza (Human Resource Management Academic Research Society, 2021)
This study examines journalistic writing styles in Covid 19 pandemic reporting on Malaysian online news portals through content analysis. The discussion is divided into research questions, such as (1) what is the pattern of the news writing style used in Covid 19 reporting on online news portals, (2) how Malaysia Kini and Malay Mail source and frame news on pandemic Covid 19. Content analysis were used to examine trends in the use of writing patterns. The study found that the writing patterns in covid 19 news delivery were descriptive, interpretative, and data journalism.